Philippine Manufacturing Health Foods Inc. a statistical quality analysis - Alberto, Raymund R.; Funesto, Jim.; Tejada, Marvin Philip (Diliman, Quezon City College of Engineering, 2000)
This study presents a documentation and evaluation of the existing quality system of Philippine Health Foods Manufacturing Incorporated (PHFMI), a nutritional drink manufacturing firm, using the tools provided by the curriculum of Industrial Quality Control. This study was accomplished by the undersigned group of Industrial Engineering students. The study was conducted with specific objectives, well within the set limitations, as stated by the group at the introductory part of the report. The group also stated how the study was to be conducted as well as the significance of this study to the company, to other industrial engineering students, and the average reader in general. The second part of the study contains a brief but concise documentation of the profile and various aspects of the company such as history, organization and the chain of the command, and the product line of PHFMI. Also included in the documentation is the process map of the manufacturing process of the company, as well as the documentation of the existing Quality System and policies of PHFMI. The study features a Failure Mode and Effect Criticality Analysis which was conducted for Enervon HP, one of the company's best selling product, to determine the primary problems the group is supposed to face. The FMECA evaluated the three major components of a finished product namely : the powder contents, pouch packaging and can packaging. From this analysis, it was determined that the fill weight, moisture content of the product, and can packaging, are the aspects most critical to the success of the product and to the customer's satisfaction. At this point, the group then directed its attentions to the three major quality problems that has troubled the company, at least from our point of view. The analysis was initiated using a streamline analysis diagram in order to identify those problems of major consideration. With this, the group determined the major problems to be defects in the powder content and packaging in general. Verifying it with the FMECA, these defects were specified as variations in fill weight, high moisture content in products, and packaging defects in cans. The causes and effects of these problems were analyzed using an Ishikawa Diagram while the processes which were plagued with these problems were examined using control charts to determine which process was really out of control. After using the x and R charts for both the fill weight and moisture content and the p-chart for the packaging defects in cans, it was found out that all these processes were out-of-control and had sources of variability not inherent to the process itself. The study was concluded with the group providing recommendations to the said problems as well as a short and somewhat general Quality Cost Analysis of the recommendations provided by the group company. For anybody wishing to continue the study, the group provided "areas for further study." Those who are interested in the other aspects of the company and keen for a deeper touch of the company's quality system, an area not totally covered by the report due to time and academic reasons, should read this section.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Philippine Manufacturing Health Foods Incorporated; Food industry and trade; Quality control